Discovering cellular protein‐protein interactions: Technological strategies and opportunities. Issue 1 (29th June 2018) - Titeca, Kevin; Lemmens, Irma; Tavernier, Jan; Eyckerman, Sven
Abstract : The analysis of protein interaction networks is one of the key challenges in the study of biology. It connects genotypes to phenotypes, and disruption often leads to diseases. Hence, many technologies have been developed to study protein‐protein interactions (PPIs) in a cellular context. The expansion of the PPI technology toolbox however complicates the selection of optimal approaches for diverse biological questions. This review gives an overview of the binary and co‐complex technologies, with the former evaluating the interaction of two co‐expressed genetically tagged proteins, and the latter only needing the expression of a single tagged protein or no tagged proteins at all. Mass spectrometry is crucial for some binary and all co‐complex technologies. After the detailed description of the different technologies, the review compares their unique specifications, advantages, disadvantages, and applicability, while highlighting opportunities for further advancements.